Network pharmacology and molecular analysis of mechanisms underlying the therapeutic effects of Rhubarb in treating atherosclerosis and abdominal aortic aneurysm - Huilin Xu; Jun Huang; Youjie Zeng; Xia Wang; Huilin Lian; Siyi Zhang; Ren Guo (Heliyon)
Aim of the study: The aim of this study was to systematically investigate the effects and mechanisms of Rhubarb in the treatment of Atherosclerosis (AS) and Abdominal Aortic Aneurysm (AAA) by utilizing network pharmacology and molecular docking techniques. Materials and methods: TCMSP systematic pharmacology database was utilized to search for active chemical components of Rhubarb. Disease-related targets were retrieved from the GEO dataset and Disgenet database. Gene interactions were utilized to identify common targets of Rhubarb with AS/AAA, and interaction networks were constructed using Cytoscape 3.9.1. Protein-protein interaction (PPI) networks for the core targets were constructed using the STRING database. GO and KEGG pathway enrichment analysis was performed using DAVID. Molecular docking is used to assess the potential target-active compound interactions. Results: In our study, 16 active compounds were screened from Rhubarb, along with 310 targets. Additionally, 110 AS/AAA target genes were screened out. Topological analysis of the PPI protein network yielded 23 core targets. The targets, biological functions and signaling pathways of Rhubarb in AS/AAA were further investigated. The analysis indicated that Rhubarb may be effective in treating AS/AAA through processes such as lipids, atherosclerosis, extracellular matrix catabolism, collagenolytic metabolic processes, and the extracellular environment. Five core pharmacological targets were also identified: TNF, IL-1β MMP9, TP53, and PPARG. Molecular docking showed a strong binding ability between the active compounds and the screened targets. Conclusions: This study successfully predicted the molecular functions, pharmacological targets, and pathways associated with Rhubarb for treating AS/AAA. In addition, identified potential active ingredients can be used as a source for AS/AAA drug screening.